The Linguistic, Stylistic and Behavioral Parallels in the Songs to Dance from Kolodiazhne in the Records of Lesya Ukrainka and the Songs to Dance (Skok) from Svitiaz'ki Smoliary (Linguostylistic Studies, 2018)
The article highlights the features of the authentic texts of the songs to dance written down by Lesia Ukrainka in her «Kolodyazhe Notebook» and on the basis of the records made by Klement Kvitka from the poetess’s voice. These sources show frequent language changes in the written text, which significantly affects first of all the authenticity of the phonetic and morphological paradigms of the original text and makes it impossible to reproduce and study the real-life speech of the Kolodiazhne inhabitants. It is for these reasons that the text of the manuscript is chosen for the analysis. The study has revealed the dominant thematic groups of dance songs in Lesia Ukrainka's records and which were fixed by the author from among the informants from Smoliary of the Svityaz area. The main criteria for their selection were the destination factor and the semantic content of the texts. The in-depth analysis of the recorded song texts has revealed that the most common song dialogues are the dialogues between men – women, girls – young fellows, wedding ceremony participants (mainly – women) – musicians. The specifics of functioning and performance of this song genre manifests itself in various family rituals. Primarily the wedding ceremony can be considered as a typical communicative situation of such actualization. The study of lexical-semantic features of the song lyrics testifies to the productive use of the typical dialect tokens to denote various everyday concepts, nominations of persons according to kinship, common folklorisms, regular epithets, comparisons, symbolic names. An analysis of the stylistic features of the reference lexemes, in particular the appeals, confirmed the inclination towards a positive vector for marking such linguistic units. The stylistics of the dance songs is marked with humorous and ironic tone, which manifest themselves primarily in the lexical plane of these texts. Such texts serve as one of the reliable sources for reconstructing the mental characteristics of the Polischuks. The comparative analysis of the songs to dance provides basis for differentiation of behavioral features of various communicators. They are the most vividly actualized in peculiar dialogues of girls –  young fellows, women – men, participants of the wedding – musicians, etc.
Keywords: songs to dance; manuscript; stylistics of songs; linguistic behavior; variability